ELEMEN-ELEMEN INTRINSIK DALAM CERITA PENDEK “PENA” KARYA RIKA - Iwan Sulistiawan, (Journal of Innovation Research and Knowledge, 2025)
This study aims to examine the intrinsic elements of Rika's short story "Pena," specifically the plot, characters and characterization, setting, and point of view. A descriptive qualitative method was used to analyze the intrinsic elements of the literary work, involving a literature review and content analysis approach. The theories used focus solely on the intrinsic elements of the literary work, referred to as the objective approach or the structural approach, which views the literary work as an autonomous, independent structure free from the influence of the author, reader, or social reality. This study found that of the four elements analyzed, three had strengths (plot, characters, and point of view), and one had weaknesses (setting).